Solid particle erosion of CVD diamond films deposited at different methane concentration; Wear; Vol. 494-495 - Gaydaychuk A. V. Alexander Valerievich; Linnik S. A. Stepan Andreevich; Mitulinsky A. S. Aleksandr Sergeevich; Zenkin S. P. Sergey Petrovich (2022, 2022)
Title screen